MOODLE SEBAGAI PENUNJANG PERKULIAHAN MENULIS KREATIF - Latif Anshori Kurniawan (Universitas Sarjanawiyata Tamansiswa, 2019)
Students still often experience obstacles in the plural writing classes in Indonesian in the classroom. The variation of constraints depends on the condition of the student. On the other hand, digital disruptions have been filling the various student activity lines. For that, we need to combine digital devices (in this context is computing software) and the learning process in the course of Creative Writing. In this article, discussed various aspects of the utilization of Moodle learning software features in the writing lecture. Moodle can be implemented offline, but not possible also online. Because it can be implemented online, resources that students use when the learning process with Moodle more abundant and attractive. The positive implications of using Moodle does not restrict students to internet service disistraksi when the online learning process, they can dig a variety of inspiration to support the quality of their writing.